SPECTROSCOPIC AND THERMAL ANALYSIS OF TiO2 BASED QUATERNARY GLASS SYSTEM - Dr.P.Shalini Priya Dharsini; Dr.S.Ponkumar (International Conference on Multidisciplinary Research Perspective, 2025)
The quaternary glass systems of B2O3 – CdO – R2O – TiO2 (R=Li, Na and K) with different compositions of TiO2 are prepared by melt - quench technique. Amorphous nature of these glasses has been confirmed from their XRD profiles. SEM analysis is carried out to study the morphological modification created by the modifier oxide. IR technique is used to investigate the structural changes with respect to composition in the glass systems and functional groups at different modification levels. Differential thermal analysis is used to identify the glass transition temperature, crystallization temperature and melting temperature of the glass samples. The glass stability factor and Hruby’s parameter are calculated from the above mentioned temperatures. The properties and structural features of glasses are discussed in terms of relative proportion as well as field strength of alkali oxide.